A multilevel investigation to reveal the regulatory mechanism of lignin accumulation in juice sac granulation of pomelo - Luning Liu; Yiran Chen; Weilin Wu; Qiuyou Chen; Zhijiao Tian; Jiakang Huang; Huaqing Ren; Jiacheng Zhang; Xi Du; Mulai Zhuang; Ping Wang (BMC Plant Biology, 2024)
Abstract Granulation of juice sacs is a physiological disorder, which affects pomelo fruit quality. Here, the transcriptome and ubiquitinome of the granulated juice sacs were analyzed in Guanxi pomelo. We found that lignin accumulation in the granulated juice sacs was regulated at transcription and protein modification levels. In transcriptome data, we found that the genes in lignin biosynthesis pathway and antioxidant enzyme system of the granulated juice sacs were significantly upregulated. However, in ubiquitinome data, we found that ubiquitinated antioxidant enzymes increased in abundance but the enzyme activities decreased after the modification, which gave rise to reactive oxygen species (ROS) contents in granulated juice sacs. This finding suggests that ubiquitination level of the antioxidant enzymes is negatively correlated with the enzyme activities. Increased H2O2 is considered to be a signaling molecule to activate the key gene expressions in lignin biosynthesis pathway, which leads to the lignification in granulated juice sacs of pomelo. This regulatory mechanism in juice sac granulation of pomelo was further confirmed through the verification experiment using tissue culture by adding H2O2 or dimethylthiourea (DMTU). Our findings suggest that scavenging H2O2 and other ROS are important for reducing lignin accumulation, alleviating juice sac granulation and improving pomelo fruit quality.